HUBUNGAN KEPATUHAN ASUPAN FE DENGAN ANEMIA DEFESIENSI BESI PADA IBU HAMIL DI PUSKESMAS SEI LANGKAI - Dino Gagah Prihadianto; Kasih Purwati; Christiana Lo (Zona Kedokteran: Program Studi Pendidikan Dokter Universitas Batam, 2026)
ABSTRACT Background: Anemia during pregnancy is a global health issue affecting nearly 50% of pregnant women worldwide. In Indonesia, the increasing prevalence of anemia reflects a persistent public health challenge. One contributing factor is poor adherence to iron tablet (Fe) supplementation. This study aimed to determine the relationship between compliance with iron tablet consumption and the incidence of iron deficiency anemia in pregnant women at the Sei Langkai Public Health Center. Methods: This was a quantitative study using a cross-sectional design. The sampling technique was accidental sampling with a total of 56 pregnant women. Data were collected through questionnaires and hemoglobin levels were measured using the Easy Touch device. Data analysis was performed using the Chi-Square test. Results: The Chi-Square test showed a significant relationship between compliance with iron tablet intake and the incidence of iron deficiency anemia (p = 0.001). Conclusion: There is a significant relationship between iron tablet compliance and the incidence of iron deficiency anemia in pregnant women at the Sei Langkai Public Health Center. Keywords: Compliance,iron Tablets,Anemia,Pregnant Women